Self-harm behavior among individuals with intermittent explosive disorder and personality disorders. (January 2015) - Jenkins, Abigail L.; McCloskey, Michael S.; Kulper, Daniel; Berman, Mitchell E.; Coccaro, Emil F.
Abstract: Self-harm behaviors are a major public health concern across the lifespan, particularly among individuals with psychiatric disorders. Little research, however, has examined these behaviors among individuals with a diagnosis characterized by recurrent acts of impulsive aggression, Intermittent Explosive Disorder (IED). Furthermore, extant research has not examined variables that might mediate the relationship between IED and self-harm. The current study examined the rates of non-suicidal self-injury (NSSI) and suicide attempts among individuals with IED as compared to healthy controls, individuals with personality disorders (PDs; which are highly comorbid with IED), and individuals with comorbid IED and PD. The study also examined the indirect effects of aggression, impulsivity, and affective lability in the relationship between diagnosis and self-harm. Participants were 1079 community individuals and prevalence rates among the total sample were 18% for NSSI and 13.2% for suicide attempts. Scores on measures aggression, impulsivity, and affect lability showed significant indirect effects on the relationships between IED + PD and NSSI; scores on aggression showed a significant indirect effect on the relationship between PD and NSSI; scores on impulsivity showed a significant indirect effect on the relationship between IED + PD and suicide attempt. These results suggest that individuals with PDs, and particularly those with comorbid IED and PD, are at increased risk for engagement in self-harm behaviors. Furthermore, traits of aggression, impulsivity, and affect lability significantly accounted for the relationship between diagnostic status and self-harm, particularly in regards to NSSI. Highlights: Comorbid IED and PD predicted history of NSSI. IED, PD, and comorbid IED and PD each predicted history of suicide attempt. Those with Comorbid IED and PD are at highest risk for self-harm behaviors. Several personality traits mediated between diagnostic group and self-harm.